Kebijakan Badan Narkotika Nasional Dalam Penanggulangan Narkoba Wilayah Perbatasan - Novana Veronica Julenta Kareth; Reni Shintasari (Musamus Journal of Public Administration, 2020)
This paper aims to determine the policies implemented by the Papua National Narcotics Agency against drug trafficking. This article is a qualitative descriptive study. Data collection methods through interviews and literature study. Data analysis using descriptive analysis model. The results showed that the role of BNN Papua is very central in the eastern region and the Indonesian border. The policies that have been planned by BNN with multi-stakeholder have been implemented, but the new modes adopted by the international network vary. The drug subscription policy cannot be carried out by one institution only, it needs to be supported by other government agencies and the community. The need for a serious role for the regional and central government in both preventive efforts and subscription programs in synergy with the Papua Provincial BNN.